Radial nerve palsy following plate osteosynthesis of shaft humerus in relation to posterior verses anterolateral approach - Patra, Bishnu Prasad; Patra, Saroj Kumar (International Journal of Research in Medical Sciences, 2016)
Background: Fracture shaft of humerus is a relatively common upper limb injury. Although it can be managed conservatively still surgical management is the recent trend worldwide. Open reduction and plate osteosynthesis is the gold standard and commonly practiced method of management. Iatrogenic radial nerve palsy following fracture fixation is a usual complication. Though most cases recover with time, but the incidence is variable in different approach. We compared two common approaches for fixation of middle 1/3rd of shaft of humerus fracture based on frequency of secondary radial nerve palsy and fracture healing. Methods: A prospective comparative study of management of all middle 1/3rd shaft humerus fracture was undertaken in our institute from Jan 2012 to Nov 2014. Total 42 patients were operated in this period of which six patients lost to follow up, so all total 36 cases were included in the study. Among these 36 patients 16 patients were operated by posterior approach and rest 20 were operated by Anterolateral approach. All patients were followed up at 2nd post-operative day, 2 weeks, 6 weeks, 3 months, 6 month and 1year. Frequency of radial nerve palsy with its outcome and fracture union was accessed in postoperative follow-ups. Results: There were total 3 cases of iatrogenic radial nerve palsy found in patients operated by posterior approach but all these patients recovered by average 5 month (3 to 6 months). There was not a single case of radial nerve palsy seen following humerus fixation by anterolateral approach. All 36 patients had good radiological union by 1 year, of which 2 patients of anterolateral approach and 1 patient from posterior approach required bone grafting to achieve union. Conclusions: Both the approaches had similar outcome in terms of fracture healing but there was significant difference in frequency of secondary radial nerve palsy, commonly seen in posterior approach.